An Empirical Study On Malaysian Ipos And Their Profit Forecasts. - Chang, Ling Foon (1998)
This paper is divided into two parts. The first part examines the trend of IPO's premiums and accuracy of profits forecasting in short run and long run. The second part examines the reputation of underwriters and size of auditors as possible determination of IPO's premium and accuracy of profits forecasting. Two hundred and forty-five new issues were analysed for the period 1993-1996. There are significant excess returns on the first day of trading with an average premium of 88 per cent. The first day lPO's premiums have a significant effect of two difference economy period. The average first day premium is about 104 per cent in the economy boom period (93-94) compared to 66 per cent in the post boom period. The results on profit forecast error showed reasonable accuracy of forecasts with an error of -2.72 per cent. Looking at the reputation of underwriters, size of auditors and the first day IPO's premium. The size of auditors and reputation of underwriters are not the determinates of the first day IPO's premium. From a sample of 137 companies after screening for outliers, 62 companies under-estimated and 75 over-estimated their profit forecasting. There is no statistically significant relationship between reputation of underwriter and size of auditor with the accuracy of profit forecasts.